TRENDS IN THE DEVELOPMENT OF SPEECH AS A COMPONENT OF THE SOUND SPACE IN MODERN CINEMA OF JAPAN / ТЕНДЕНЦИИ В РАЗВИТИИ РЕЧИ КАК КОМПОНЕНТА ЗВУКОВОГО ПРОСТРАНСТВА В СОВРЕМЕННОМ КИНЕМАТОГРАФЕ ЯПОНИИ - OBRUCHNIKOV I.М. / ОБРУЧНИКОВ И.М. (Наука телевидения, 2016)
On the example of the films of Japanese directors, Midzoguchi, K., S. Fukui, S. Ishii, S.Tsukamoto, the article considers speech as a specific element of the sound space in the film. The author comes to the conclusion that in Japanese films, in particular, through flexible interpenetration of sound textures, sound space seeks to recreate the sound continuum. In this case, it is possible to speak about the strengthening of the descriptive principle of modern Japanese cinema sound.